In Vitro and In Silico Studies of Quercetin and Daidzin as Selective Anticancer Agents - Muhammad Sulaiman Zubair; Syariful Anam; Saipul Maulana; Muhammad Arba (Universitas Gadjah Mada, 2021)
Quercetin and daidzin are flavonoid and flavonoid glycoside type compounds that have been found in many plants and nutraceuticals. This study aims to examine the in vitro cytotoxic and selectivity properties of quercetin and daidzin on breast and cervical cancers and to study their molecular interaction and stability on epidermal growth factor receptor tyrosine kinase (EGFR-TK) by applying molecular docking and molecular dynamics (MD) simulations. In vitro anticancer activity was performed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method on breast cancer cell (T47D), cervical cancer cells (HeLa), and Vero normal cells, while molecular docking and MD simulation were done by using AutoDock Vina and Amber18 package software, respectively. Quercetin and daidzin showed potent cytotoxic and high selectivity on both cell lines. Daidzin was found to has a higher IC50 and selectivity index than quercetin. Docking and MD results showed that both compounds prefer to interact with epidermal growth factor receptor tyrosine kinase (EGFR-TK). Daidzin showed better interaction than quercetin with a docking score of -9.6 kcal/mol. Also, daidzin was found more stable than quercetin with low RMSD and RMSF values.